2013
DOI: 10.1094/pdis-11-12-1014-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Powdery Mildew (Pseudoidium anacardii) of Mango Trees in Sinaloa, Mexico

Abstract: Powdery mildew of mango is an important disease in Mexico's northern Sinaloa state. Identification of the causal fungal agent has been hindered by the absence of information regarding its teleomorph, as well as a detailed morphometric analysis of the anamorph and molecular characterization. The first symptoms of the disease appear in mango inflorescences of early February, and it subsequently affects young fruits. The disease progresses during March and early April, causing significant fruit abortion and a sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
7
0
4
Order By: Relevance
“…Cook with E. quercicola as a teleomorph (Félix-Gastélum et al, 2013). As in other mangoproducing areas of the world (Nasir et al, 2014), in northern Sinaloa the teleomorph was not found in specimens collected in mango vars.…”
Section: Mildew In Mangomentioning
confidence: 79%
See 3 more Smart Citations
“…Cook with E. quercicola as a teleomorph (Félix-Gastélum et al, 2013). As in other mangoproducing areas of the world (Nasir et al, 2014), in northern Sinaloa the teleomorph was not found in specimens collected in mango vars.…”
Section: Mildew In Mangomentioning
confidence: 79%
“…As in other mangoproducing areas of the world (Nasir et al, 2014), in northern Sinaloa the teleomorph was not found in specimens collected in mango vars. Kent and Keith in commercial or backyard orchard trees (Félix-Gastélum et al, 2013). In other parts of…”
Section: Mildew In Mangomentioning
confidence: 99%
See 2 more Smart Citations
“…Mango powdery mildew caused by Erysiphe quercicola (anamorph: Pseudoidium anacardii) (Braun and Cook, 2012;Félix et al, 2013;Tam, 2017) is one of the most important diseases that affects mango because of its high level of severity, endemism and cosmopolitan distribution (Raheel et al, 2008) La cenicilla del mango, causada por Erysiphe quercicola (anamorfo: Pseudoidium anacardii) (Braun y Cook, 2012;Félix et al, 2013;Tam, 2017) es una de las enfermedades más importantes de este frutal por su alta severidad, endemismo, distribución cosmopolita (Raheel et al, 2008) y causar pérdidas de cosecha de 80-90% (Gupta, 1989b;Shoeman et al, 1995;Nasir et al, 2014). En entidades federativas exportadoras de mango como Michoacán puede afectar el 60% de los árboles comerciales, representando 30-50 mil ton de fruta (Arias et al, 2004) y en Sinaloa ocasionar pérdidas de 70% durante floración (Félix et al, 2017).…”
unclassified